4(11x-49)=4-2(x+5)

Simple and best practice solution for 4(11x-49)=4-2(x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(11x-49)=4-2(x+5) equation:


4 (11x-49)=4-2 (x+5)

We simplify the equation to the form, which is simple to understand
4(11x-49)=4-2(x+5)

Reorder the terms in parentheses
+(+44x-196)=4-2*(x+5)

Remove unnecessary parentheses
+44x-196=+4-2+*(+x+5+)

Reorder the terms in parentheses
+44x-196=4+(-2x-10)

Remove unnecessary parentheses
+44x-196=+4-2x-10

We move all terms containing x to the left and all other terms to the right.
+44x+2x=+4-10+196

We simplify left and right side of the equation.
+46x=+190

We divide both sides of the equation by 46 to get x.
x=4.1304347826087

See similar equations:

| 89=c+44 | | b+13=56 | | x+x*0.48=785.83 | | 13n=117 | | m-76=158 | | 7.9+x=12.3 | | 4x(x-3)+2x-x^2=3x^2+40 | | X=17-13 | | x^3-2x=-x | | x+8.9=9.7 | | 8x-8=-11 | | X=25-15 | | 8c-(3c+2)= | | 10x+7-4x=-8x-30+x | | 21=x-43 | | 2(2x+2)=-(2x+2) | | x+x*0.5=200 | | 0.5x+23=-15 | | xc-d=0 | | X/7=-1/2 | | 4x-10=98 | | 3(3x-1)+5=6(X+2) | | F(x)=2x-16x+31 | | 3x^2-7x-21=-1 | | 4(x-2)=5x+17 | | -4-7(5x-7)=49-39x | | x-89=176 | | 2q-5=8q+1 | | X+52+90+90=360 | | x^2-X=43.32 | | 40=-5m-5 | | 64+x=146 |

Equations solver categories